Modeling framework for simulating concentrations of solute chemicals, nanoparticles, and solids in surface waters and sediments: WASP8 Advanced Toxicant Module. (January 2019) - Knightes, Christopher D.; Ambrose, Robert B.; Avant, Brian; Han, Yanlai; Acrey, Brad; Bouchard, Dermont C.; Zepp, Richard; Wool, Tim
Abstract: Toxicant concentrations in surface waters are of environmental concern due to their potential impacts to humans and wildlife. Numerical models provide system insight, support management decisions, and provide scenario testing on the impacts of toxicants. The Water Quality Analysis Simulation Program (WASP) is a widely used framework for developing site-specific models for simulating toxicant concentrations in surface waters and sediments over a range of complexities and temporal and spatial scales. WASP8, with the Advanced Toxicant module, has been recently released, incorporating a complete architecture redesign for an increased number of state variables and different state variable types. WASP8 incorporates a new structure for simulating light intensity and photoreactions in the water column, including the distinction of 10 different wavelength bands, and nanoparticle heteroaggregation to solids. We present a hypothetical case study, using the Cape Fear River, North Carolina as a representative example for simulating solute chemicals, nanoparticles, and solids to demonstrate the new and updated capabilities of WASP8. Highlights: Water Quality Analysis Simulation Program (WASP) is widely used across the US and world for contaminants in surface waters. Updated WASP8 architecture: Advanced Toxicant module has increased state variable types, state variables, and processes. Nanoparticles have been added as a new state variable with heteroaggregation kinetics. Improved light module simulates light intensity and attenuation for 10 specific wavelength bands with photoreactions. A hypothetical case study demonstrates the new and updated capabilities of WASP8.